Pengaruh Kepercayaan Konsumen, Kualitas Produk, dan Kualitas Informasi terhadap Minat Beli Tiktok Shop di Kediri - Amasya Permata Hana Purwa; Brahma Wahyu K; Kukuh Harianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the effect of work discipline, work motivation, and work environment on employee performance at PT. Yara Berkah Semesta Kediri. The research employed a quantitative approach with a survey method by distributing questionnaires to 50 employees, who were selected as the sample using a census technique. The data analysis techniques used in this study included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, and F-test, with the assistance of SPSS software. The results revealed that, partially, work discipline and work motivation did not have a significant effect on employee performance, while the work environment had a positive and significant effect. Simultaneously, work discipline, work motivation, and work environment had a positive and significant effect on employee performance, with an F-value of 32.586 and a significance level of 0.000. These findings indicate that employee performance improvement is more strongly influenced by a supportive and comfortable work environment. Therefore, the company is advised to reconsider its strategies for enhancing discipline and motivation, while maintaining a conducive work environment to support productivity. The practical implications of this study suggest that organizations should prioritize creating and maintaining a positive work environment as a fundamental strategy to boost performance. Additionally, companies need to design interventions that strengthen employee discipline and motivation, such as recognition programs, training, and clear performance management systems, while ensuring that these efforts are integrated with improvements in the work environment.